MAPPING THE SPATIAL VARIATION OF RIVERS WATER QUALITY USING MULTIVARIATE ANALYSIS. A CASE STUDY OF GREATER JAKARTA, INDONESIA - Ramadhani Yanidar; Djoko Mulyo Hartono; Setyo Sarwanto Moersidik; Yves Andres (Universitas Trisakti, 2023)
Urban activities and runoff deteriorated the river water. Aim: This study aims to determine the primary contamination and mapping river's water quality variation in Greater Jakarta. Methodology and Results: Multivariate analysis was employed by Factor Analysis and Cluster Analysis (FA and CA) using the 12 parameters of the water quality dataset from 76 sampling stations in 19 rivers in the Greater Jakarta Region, Indonesia, between 2014 and 2015. The FA result showed that almost 66.6% of the total variance in water quality data was associated with four significant variators of which 36.12% identified the main parameters BOD, COD, TP, ammonia, nitrate, and detergent. The cluster analysis grouped the sampling locations into 3 (three) clusters to indicate the spatial classifications of river water. Cluster 1 indicates pollutants from the residential area, Cluster 2 from residential and commercial areas, while Cluster 3 is majorly pollutants from industrial areas. Conclusion, significance, and impact study: The results showed the conductivity and TDS concentrations in cluster 3 are higher than the others since most of the sampling points are located near an industrial area or downstream close to the estuary. The mapping gave a better understanding of the river water quality characteristic spatially and could assist local governments in prioritizing river pollution management.